Effects of group human behaviour on the modelling of fire evacuation in modern buildings - Wang, Yang. (2010)
With the development building technology, huge, and multi-function buildings are now more familiar since they are more economical. But at the same time, catastrophes which occurred them now can easily cause big loses, thus simulation of evacuation in modern buildings is attracting more and more attention. A cellular automata (CA) model, which adopts the findings of human behavior exhibited by people who are located in the buildings, is proposed to simulate the emergency evacuation in a specifically building. CA has been successfully applied to simulate various complex systems, such as traffic flow and fluids. It has also been introduced to the simulation of pedestrian flow and the success motivates researchers to further extend CA to emergency evacuation since both areas are similar.